Kajian tentang Jumlah Kuadrat dan Hasil Kali dalam Analisis Varians Multivariat - Hafnani, Marzuki, (Universitas Bengkulu, 2014)
Multivariate analysis of variance is the generalization analysis of variance. Two-way multivariate analysis of variance is to know two-way effects of ???? criteria variables with ???? ? 2. The matrix of sum of squares and cross-product or matrix of JKHK total is rather same with sum of squares total at univariate situation divided four JKHK matrices that has mean, each JKHK factor A, factor B, interaction between factor A and factor B, and JKHK error. With pass comparative determinant of JKHK error matrix to determinant of sum of matrices JKHK factor that we want to know the effects and JKHK error, it can be found a statistic ????? that is know as Wilks’ Lambda.